The method to improve the accuracy of experiment using helium instead of hydrogen - Chen, Lihua; Hong, Yingchen; Qi, Wei; Yao, Zhanhui; Jiang, Xiaolong; Zhao, Ziming; Li, Yuejuan (International journal of hydrogen energy, 2024)
Based on the hydrogen-helium similarity theory, the leakage experiments using helium instead of hydrogen can effectively reduce the risk of hydrogen deflagration, but the experimental results show that there is a large difference between the concentration of hydrogen and helium in initial period of leakage base on this theory. This paper focuses on leakage experiments under turbulent conditions in enclosed spaces. Based on the hydrogen-helium similarity theory, helium is used to replace hydrogen to find out the concentration of helium at multiple leakage speeds. A comparison is made between helium concentration values and hydrogen concentration values, and a polynomial correction algorithm is used to shrink the difference. The results show that this correction method can reduce the concentration average error between the helium and the hydrogen from 14.06% to 7.94% for the Reynolds number range of 3500–9500. Therefore, a polynomial fitting algorithm based on this theory can improve the accuracy of experiment using helium instead of hydrogen. •Analyzed the accuracy of the hydrogen helium similarity theory under some working conditions in the experiment.•Proposed a correction method for helium concentration, which can improve the accuracy of using helium instead of hydrogen in experiments.•The improvement effect of using this correction method is significant.•This study can offer support in the formulation of regulations pertaining to hydrogen safety development.